Inhibitory effects of fruit extracts on nitric oxide-induced proliferation in MCF-7 cells - Jayakumar, R.; Kanthimathi, M.S. (2011)
Nitric oxide is a free radical involved in the pathogenesis of cancer by increasing tumour vascularization and metastasis. Studies using nitric oxide inhibitors have shown decrease in tumour growth and a role in cancer therapy. To analyse the effect of fruits on nitric oxide, we carried out experiments using a nitric oxide donor on the breast cancer cell line, MCF-7. Proliferating MCF-7 cells were treated with the methanolic extract of the fruits. The inhibitory activity of fruit extracts on cell proliferation was measured using the MTT assay. Chiku and dragon fruit showed high inhibitory activity when compared to the other fruits tested. The total polyphenol and flavonoid content and nitric oxide scavenging activity were found to be high in pomegranate, chiku, litchi, durian, grape and apple. This study shows that phytochemicals present in fruits scavenge nitric oxide and inhibit MCF-7 cell proliferation. Â© 2010 Elsevier Ltd. All rights reserved.